2007
DOI: 10.1042/bj20070195
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of stress-induced intracellular sorting and chaperone function of Hsp27 (HspB1) in mammalian cells

Abstract: In vitro, small Hsps (heat-shock proteins) have been shown to have chaperone function capable of keeping unfolded proteins in a form competent for Hsp70-dependent refolding. However, this has never been confirmed in living mammalian cells. In the present study, we show that Hsp27 (HspB1) translocates into the nucleus upon heat shock, where it forms granules that co-localize with IGCs (interchromatin granule clusters). Although heat-induced changes in the oligomerization status of Hsp27 correlate with its phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
84
0
9

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(95 citation statements)
references
References 49 publications
2
84
0
9
Order By: Relevance
“…In protein refolding assays in vitro (Horwitz, 1992; Jakob et al ., 1993), aggregation prevention by the ATP‐independent small HSPs has been shown to occur independent of the ATP‐dependent HSP70 machinery, but for efficient refolding, substrate transfer to the HSP70 machine is required (Lee & Vierling, 2000; Mogk et al ., 2003). Also, in living cells, refolding assistance by HSPB1 was found to require a functional HSP70 machinery (Bryantsev et al ., 2007), and in this study, a similar scenario was found to be true for the best refolding stimulating D. melanogaster small HSP, CG14207. Strikingly, CG14207 was ineffective in preventing polyQ aggregation.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In protein refolding assays in vitro (Horwitz, 1992; Jakob et al ., 1993), aggregation prevention by the ATP‐independent small HSPs has been shown to occur independent of the ATP‐dependent HSP70 machinery, but for efficient refolding, substrate transfer to the HSP70 machine is required (Lee & Vierling, 2000; Mogk et al ., 2003). Also, in living cells, refolding assistance by HSPB1 was found to require a functional HSP70 machinery (Bryantsev et al ., 2007), and in this study, a similar scenario was found to be true for the best refolding stimulating D. melanogaster small HSP, CG14207. Strikingly, CG14207 was ineffective in preventing polyQ aggregation.…”
Section: Discussionsupporting
confidence: 80%
“…In vitro , the addition of the HSP70/HSP40 refolding machinery is required for the refolding reaction (Lee et al ., 1997). This has been reproduced in living cells using luciferase as a substrate (Nollen et al ., 2001; Bryantsev et al ., 2007). Here, we tailored the cellular luciferase refolding assay for Drosophila S2 cells and characterized which of the Drosophila small HSPs could enhance luciferase refolding upon overexpression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hsp27 is thought to play a role in protecting the myocardium during periods of stress and linkage analysis suggested hsp27 as a determinant of heart mass in spontaneously hypertensive rats [37]. The actin-capping, aggregation and, possibly molecular chaperone function, of hsp27 are regulated by phosphorylation (see [8,10]). The expression and/or phosphorylation of hsp27 in the heart is increased in response to chronic pressure overload [20], both physiological and pathological hypertrophy [13], heart failure [21,38,39], oxidative stress [24,25], ischemic injury [22], and haemorrhagic shock [23].…”
Section: Discussionmentioning
confidence: 99%
“…Hsp27 function appears to be regulated by posttranslational modifications, including phosphorylation at Ser-18, Ser-78, Ser-82, and Thr-143 [8,2]. Phosphorylation promotes the dissociation of hsp27 oligomers [9] and phospho-mimetic hsp27 mutants (i.e., S-15,78,82-D) show enhanced chaperone activity [10]. Furthermore, when phosphorylated, hsp27 dissociates from F-actin and may bind laterally to, and stabilize, actin filaments [7,11].…”
Section: Introductionmentioning
confidence: 99%